Kritik terhadap Implementasi Kurikulum Merdeka: Kompetitif dan Administratif dalam Perspektif Paulo Freire - Syukron Hidayat, Muhamad (Paedagogie, 2025)
This study aims to identify key challenges in the implementation of the Merdeka Curriculum and examine them through Paulo Freire’s critical pedagogy. Using a literature review method, the study analyzes recent empirical findings related to assessment practices, teachers’ administrative workload, the implementation of the Pancasila Student Profile Project (P5), and teacher readiness. The results show four major issues: unbalanced assessment practices reinforcing banking education, the dehumanization of teachers through excessive administrative demands, the procedural reduction of P5, and the gap between curricular ideals and teachers’ practical capacity. The study concludes that these challenges are structural and require comprehensive support, including training, administrative simplification, and the strengthening of dialogic and reflective pedagogical practices to ensure that the Merdeka Curriculum aligns with its humanistic and transformative goals.